Pellets plásticos em praias do litoral do Ceará: influência de atividades antropogênicas - Fonsêca, Letícia Monteiro da (2024)
Plastic pollution is a growing global problem, as it poses a major threat to marine and coastal ecosystems. In particular, microplastics (particles ranging from 1 μm to 5 mm) are threatening because they can be ingested or absorbed by the biota, and carry toxic chemicals. Microplastics include pellets, thermoplastic resins in granulated form, used as raw material by the plastic processing industries. These granule sizes range from 2 to 5 mm and they are released into the environment during their production, transport, and storage. Pellets are normally originated from port facilities and industrial areas, and they consist of persistent materials that cause negative impacts on marine fauna through ingestion and chemicals leaching. This study aimed to detect plastic pellets on beaches of the state of Ceará, characterize their morphology and polymeric composition, and quantify some organic contaminants associated with them. Eight beaches distributed across the coast of Ceará were selected: Praia do Porto, Cumbuco, Iparana, Meireles, Praia do Futuro, Pontal do Maceió, Canoa Quebrada, and Icapuí. Two sampling surveys were conducted, in the dry (second half of 2022) and wet (first half of 2023) periods. The sampling consisted of active search, where the pellets were searched for one hour on the surface of the sand, in the upper portion of the intertidal zone and lower portion of the supralittoral. The pellets were initially quantified and characterized considering size, color, and shape. To identify the types of polymers, RAMAN spectroscopy was used. The following organic contaminants associated to the pellets were analyzed: polychlorinated biphenyls (PCBs), polybrominated diphenyl esters (PBDEs), pyrethroids (PPs), and organochlorines (OCPs). They were analyzed by gas chromatography coupled to an electron capture detector (CG-ECD). 1086 pellets were found on the surface sediments of the sampled beaches, 649 corresponded to the rainy period of 2023, and 437 to the dry period of 2022. The most common morphology found was spherical, followed by flattened spherical, and flattened cylindrical. The most frequent colors were white, yellow, and gray and the most common types of polymers were polyethylene (PE) and polypropylene (PP). The total concentrations of POPs in the pellets ranged from 72.8 to 6289.6 ng/g for PCBs, 93.6 to 1051.6 ng/g for PBDEs, 259.1 to 2912.8 ng/g for PPs, and 50.3 to 1338.3 ng/g for OCPs. It was concluded that environmental and anthropogenic factors affect the distribution and deposition of pellets across the coast of Ceará, and that the concentrations of contaminants were extremely high. However, no consistent patterns related with gradients or defined seasonality could be observed.